Climate Change Awareness of the Community Officials in the Municipality of Saint Bernard, Southern Leyte: Gear towards Vulnerability and Adaption - Garcia, Gary C. (JPAIR Multidisciplinary Research, 2013)
Eastern Visayas is constantly experiencing a series of calamities since the tragic mudslide in the community of Guinsaugon Saint Bernard, Southern Leyte in 2006. As a result, the state of calamity declared in almost every part the country due to heavy rains that devastated agriculture, livestock and properties. This study was conducted to assess the level of the community officials' related awareness on climate change, more particular on its cause and effect, thought and belief, and the course of action through community ordinances related to climate change. The study utilizes the descriptive survey method of research. Data was analyzed and interpreted using weighted mean and percentages to describe the level of awareness of the elected officials towards climate change. Majority agreed that climate change is happening and presently affecting the people in the community. Thought of respondents towards climate change is highly coupled with religious thinking. Actual state of affairs (situation) is the priority of the community officials leading to the inaccurate expectation of the long term effect of climate change. Community officials' awareness on the causes and effect of climate change is observable but limited on vulnerability and adaptation. Thus, additional exposure and depth understanding on climate change is recommended.
Keywords: Climate change; awareness; political and social responsibilities; descriptive-survey; Saint Bernard; Southern Leyte; Philippines